Indians, markets, and rainforests : theory, methods, analysis - Godoy, Ricardo A., 1951- (Columbia University Press, 2001)
Godoy investigates five lowland Amerindian societies of tropical Latin America--all of which are experiencing deep changes as they modernize--to discover the results of a market economy on both indigenous peoples and the conservation of tropical rainforest flora and fauna.